2003
DOI: 10.1523/jneurosci.23-04-01478.2003
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Functional Neuron Group for Respiratory Rhythm Generation in the Ventral Medulla

Abstract: We visualized respiratory neuron activity covering the entire ventral medulla using optical recordings in a newborn rat brainstem-spinal cord preparation stained with voltage-sensitive dye. We measured optical signals from several seconds before to several seconds after the inspiratory phase using the inspiratory motor nerve discharge as the trigger signal; we averaged the optical signals of 50-150 respiratory cycles to obtain an optical image correlating particularly to inspiratory activity. The optical image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
435
4
7

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 481 publications
(472 citation statements)
references
References 28 publications
24
435
4
7
Order By: Relevance
“…These data provide evidence of a second rhythm generator (expiratory), which is only expressed with depression of the inspiratory rhythm generator. This expiratory rhythm generator is rostral to the pre-BötzC area ventrolateral to the rostral Bötzinger complex and/or in the parafacial region (4,8,14,17). In goats during the tachypneic period following IA injections, rhythmic abdominal muscle activity was clearly present, and it was characteristically 180°o ut of phase with diaphragm activity.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…These data provide evidence of a second rhythm generator (expiratory), which is only expressed with depression of the inspiratory rhythm generator. This expiratory rhythm generator is rostral to the pre-BötzC area ventrolateral to the rostral Bötzinger complex and/or in the parafacial region (4,8,14,17). In goats during the tachypneic period following IA injections, rhythmic abdominal muscle activity was clearly present, and it was characteristically 180°o ut of phase with diaphragm activity.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, in vivo studies in anesthetized or decerebrate cats or rats demonstrate that lesioning of the pre-BötzC results in transient (24) or irreversible (7, 10, 18) elimination of eupneic respiratory activity. Further demonstrating the importance of the pre-BötzC in control of breathing was a study showing that Ͼ80% destruction of neurokinin-1 receptor (NK1R)-expressing neurons in the pre-BötzC resulted in an ataxic breathing pattern and hypoventilation in awake rats (6).Recently, it has been proposed that, within the medulla, there are two respiratory rhythm generators, which are mutually inhibitory and each capable of generating a rhythm under different conditions: one is an inspiratory generator composed of pre-BötzC inspiratory neurons, and the second is an expiratory generator composed of preinspiratory (pre-I) neurons ventrolateral to the rostral Bötzinger complex (4,8,14,17). Supposedly, the pre-BötzC rhythm generator is normally dominant, and it inhibits the rostral pre-I neurons (14), which initiate rhythmic abdominal muscle contraction when preBötzC inspiratory neuronal activity is depressed (4, 8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Respiration is proximally controlled by central pattern generator (CPG) nuclei in the brain stem (Feldman and Ellenberger 1988;Mellen et al 2003;Onimaru and Homma 2003), which integrate a variety of descending inputs from cortical and subcortical structures (Gaytan and Pasaro 1998). Studies in anesthetized animals and in vitro preparations have shown that respiratory patterns can be finely controlled by afferent input (Arata et al 2000;Morris et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Both regions are rich in respirationmodulated neurons, and have been proposed as playing a critical role in respiratory rhythm generation (Janczewski and Feldman, 2006;Onimaru et al, 1988;Onimaru et al, 2006;Smith et al, 1991). Low spatial resolution optical recordings from the en bloc brainstem spinal cord preparation (Onimaru and Homma, 2003) indicated that the pFRG lay lateral to the preBötC, and provided a starting point for the parametrization of a sagittal slab preparation. Parameters that exposed both networks were arrived at iteratively (across many preparations) by adjusting ventrodorsal and rostrocaudal tilt, and mediolateral level of section so as to isolate a preparation that displayed Ca ++ signals at the level of the pFRG and preBötC, and that generated a stable respiratory rhythm at physiological…”
Section: Introductionmentioning
confidence: 99%